Characterization of an inositol-producing Lactobacillus plantarum strain and the assessment of its probiotic potential and antibacterial activity. (January 2022) - Fu, Bing; Huang, Xingxing; Ma, Jian; Chen, Qingwei; Zhang, Qili; Yu, Ping
Abstract: The compound inositol has many important applications in various fields. However, no information can be obtained on the biosynthesis of inositol by lactic acid bacteria (LAB) so far. In this study, an inositol-producing Lactobacillus plantarum ZJ2868 was isolated and identified, and its probiotic potential and antibacterial activity were assessed. The isolated L. plantarum ZJ2868 strain produced 33.66 ± 0.75 mg/L of inositol. The optimal temperature and pH for the strain growth were 30 °C and 6.0, respectively. This strain could resist high osmotic pressure, and grew well in Man Rogosa Sharpe (MRS) medium with 6% NaCl. It displayed a strong acid resistance, and the number of viable cells was over 93.9% on the conditions of pH 3.0 and 3.5 for 4 h. 59.8% cells could survive at a high bile salt concentration of 0.1% for 1 h. This strain exhibited an obvious inhibitory effect on Pseudomonas fluorescens and Listeria monocytogenes, and was sensitive to amoxicillin and ampicillin. These findings broaden the use of LAB and deepen our understanding of LAB as potential producer of inositol. Highlights: An inositol-producing Lactobacillus plantarum was isolated and identified. The isolated strain showed high osmotic pressure, acid and bile salt resistance. The isolated strain had an obvious inhibitory effect on five food pathogens. The isolated strain showed high sensitivity to amoxicillin and ampicillin.